Penebusan Hanya Oleh Darah Anak Domba Allah (Yesus Kristus) 1 Perus 1:18-19 - Yoram H. A Tuan; Abad Jaya Zega (Publisher STPKat, 2023)
God created the first humans, namely Adam and Eve, both were created in the image and likeness of God and there was no sin in them, but Adam and Eve ultimately fell into sin because of human greed and violating what God commanded. They ate the fruit from the tree of the knowledge of good and evil which God had forbidden them to eat. Because when they eat it they die and death is what makes humans sin and lose the glory of God from themselves. In the book of Romans 3:23, it says